2000
DOI: 10.1121/1.4743813
|View full text |Cite
|
Sign up to set email alerts
|

Horizontal angular discrimination by an echolocating bottlenose dolphin (Tursiopstruncatus)

Abstract: A bottlenose dolphin was tested on its ability to echoically discriminate horizontal angular differences between two arrays of vertical, air-filled PVC rods. The blindfolded dolphin was required to station in a submerged vertically oriented hoop 2 radial meters from the stimuli and indicate if an array with four rods (S+) was to the left or the right of an array with two rods (S−) by pressing a corresponding paddle. The rods within each array were separated by 2 deg and the two arrays were separated by eight d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Absence of the directivity non-coherent pulses is caused due to natural necessity in broadcast transmission both the phonemes and probing pulses. Whereas the directional reception both the echo-signals and dolphin speech from all directions around of a dolphin can be performed by a new external ear [8][9][10][11] with the localization accuracy of 1˚ -3˚ [49][50][51].…”
Section: Discussionmentioning
confidence: 99%
“…Absence of the directivity non-coherent pulses is caused due to natural necessity in broadcast transmission both the phonemes and probing pulses. Whereas the directional reception both the echo-signals and dolphin speech from all directions around of a dolphin can be performed by a new external ear [8][9][10][11] with the localization accuracy of 1˚ -3˚ [49][50][51].…”
Section: Discussionmentioning
confidence: 99%
“…The primary use of the eye cups was not to force the dolphin to use echolocation, but to prevent her from attending to visual distractions that appeared to be a problem during the training phase of this experiment. Eye cups are routinely used in echolocation studies that have shown dolphins can discriminate and recognize objects, and can navigate through their environment without the use of vision [ 35 – 37 ].…”
Section: Methodsmentioning
confidence: 99%
“…, ), thus demonstrating that through echolocation, dolphins can appreciate the spatial structure of objects. An ability to make fine angular discriminations by echolocation (Branstetter et al . , ). An ability to demonstrate an awareness of its own actions (Mercado et al . , ), thus revealing new dimensions of dolphin self‐awareness beyond mirror‐self recognition (Reiss and Marino ). An ability to understand human directed referential pointing at distally placed objects; a skill which comes easily to the dolphin (Herman et al .…”
Section: Biographymentioning
confidence: 99%
“…• An ability to make fine angular discriminations by echolocation (Branstetter et al 2003(Branstetter et al , 2007.…”
Section: Biographymentioning
confidence: 99%